Da emancipação negra a emancipação humana: política de promoção da “igualdade racial” e superação do racismo. - SANTOS, Rosenverck Estrela (2021)
In the context of the neoliberal globalization of the late 20th and early 21st centuries, race, identity and racism became central themes of debate, tensions, disputes, inequalities and conflicts in practically all parts of the globe. In Brazil, substantially characterized by almost four hundred years of enslavement, it would be no different, as race and racism were essential in the particularity of our dependent capitalist social formation, delimiting social and racial hierarchies, but also a Eurocentric and racist mentality. In neoliberalism, all this has deepened, combined with productive restructuring, the “flexible accumulation of capital” and the attack on the social rights of the working class. The black population, in the fight against racism, and the organized entities of the black movement, in the demand for social rights and "racial equality", demanded from the State and from the governments the implantation and implementation of policies centered on the racial cut that would solve the black question in Brazil, that is, with the objective of building a set of actions to promote “racial equality”. The present thesis discloses the result of the analysis of the policy of promotion of “Racial Equality” between 2003 and 2016, from the perspective of the concepts of human emancipation and social equality. Guided by the qualitative, bibliographic and documentary analysis and based on historical-dialectical materialism, this research analyzes the theoretical foundations and assumptions and political practices of the institutionalization of the policy of "promotion of racial equality" and its possibilities of guaranteeing or not the equality of race for the black population. The genesis of racially-based public policies is diachronically and synchronously contextualized. It is also discussed how these policies are connected and confronted with the aspirations of the black movement entities and of the State, who at the same time appropriates the demands of the movements and denies them in their entirety. It is stressed how social policies and racism have a structural relationship with the capitalist mode of production. It was found that racism and capitalism cannot be separated and that the birth, consolidation and expansion of this mode of sociability are indebted to the slave trade in Africa, the exploitation of wealth and the indigenous genocide in America and, as a result, the entire set of racist elaboration on non-European peoples. The Brazilian social formation and its nexus with the racial issue are contemplated, discussing the myth of racial democracy and the policy of whitening in the constitution of social inequality. It examines the relationship between the globalization of capital and the great importance that the politics of identity and diversity had in the world since then. Discussions, actions and contradictions of the proposals and initiatives of the entities of the black movement are evaluated, in their plurality, demarcating their importance in the anti-racist movement and in the constitution of the so-called public policy of promotion of “racial equality”. Finally, it was sought to unveil the theoretical assumptions and political practices – by means of legislation, programs, decrees, state plans, etc. – which underlie these proposals for overcoming racial inequality, at the same time that, identifying their limits, the necessary conditions are presented – by the search for human emancipation and social equality – for this policy to be fully successful.